Neutron diffraction and the residual stress distribution of magnesium processed by equal channel angular pressing. (January 2020) - Rifai, Muhammad; Mujamilah,; Muslich, Muhammad Refai; Ridwan,; Sarr, Mouhamadou Moustapha; Miyamoto, Hiroyuki
Abstract: Neutron diffraction and the residual stress distribution of magnesium processes by equal channel angular pressing was investigated in term of the grain refinement process. Magnesium is one of the metallic material for a biomedical implant due to the biodegradable properties. The structure and strength of biodegradable metallic material are quite essential to discuss for biomedical implant purposes. The ultrafine-grained structure of magnesium was prepared by equal channel angular pressing until four passes by route Bc at 523 K. The specimen was characterized by electron backscattering diffraction for the structure and neutron diffraction for residual stress. The grain refinement happened during the equal channel angular pressing on magnesium. The texture after four passes of ECAP shows a random orientation compare to coarse grain. The result shows that the strength of the ultrafine grain structure is lower than the coarse grain structure due to the crystal structure of magnesium as hexagonal. The other reason is that the distribution of residual stress on ultrafine grain bulk specimens, which measured by neutron scattering facilities.